Two new species of Interphasma Chen & He, 2008 (Phasmatodea: Phasmatidae: Clitumninae) from Yunnan, China - Liu, Yi-Fan; Yang, Sheng-Chuan; Gu, Jun-Jie; Wang, Hai-Jian (Zootaxa, 2024)
Two new species of Interphasma Chen & He, 2008 are described in this article from Yunnan, China. Interphasma monticola sp. nov., is characterized by a ridge-shaped praeopercular organ with distinct median carina on the posteromedian area of seventh abdominal sternum. I. carinata sp. nov. is characterized by distinct longitudinal carinae of meso- and metanotum in female and pronotum rectangle in both sexes.